Morphological Characteristic of Adult Armigeres subalbatus from Sumbersari Jember - Nihayah, Husnatun; Purwatiningsih, Purwatiningsih (BERKALA SAINSTEK, 2023)
Armigeres subalbatus is a type of mosquito that is widely distributed in the world, including Jember Regency, Indonesia. The larval natural habitat is mainly found in trees that can hold water, adult mosquitoes can be found indoors or outdoors. In the field of health, Ar. subalbatus acts as a vector for filariasis, Japanese Encephalitis (JE) and zika. This study aims to identify the morphological characteristics of the Ar. subalbatus from Sumbersari Village, Jember Regency. Although in Indonesia there is no significant evidence of the role of Ar. subalbatus in the health sector, it is important to detect the morphological features of Ar. subalbatus to be able to detect mosquitoes properly. Knowing the exact type of mosquito can provide consideration for appropriate mosquito control methods. The method used is through the installation of ovitrap in November 2022. The ovitrap media is in the form of tap water, the ovitrap is left for 8 days. Ar. mosquitoes were found in the larval stage of the ovitrap. The larvae were brought to the Jember University Faculty of Mathematics and Natural Sciences Zoology Laboratory for hatching and data collection on the morphological characteristics of mosquitoes. The results of this study include the morphological characteristics used for the identification of Ar. subalbatus which includes the shape of the proboscis, flagelomeres on the palps, color of the scutum, border of the scutum, size of the antepronotum, bands on the pleura, prespiracular and postspiracular areas, edges of the mesepimeron, abdomen (tergum, sterna), apex of the femur, venation of the wings, alula and upper calypter of the wings.